2010
DOI: 10.3989/revmetalm.1008
|View full text |Cite
|
Sign up to set email alerts
|

The origins of strengthening in nanostructured metals and alloys

Abstract: Nanostructured metals and alloys have a variety of chemical and physical properties that are greatly modified by the nano-scale of their microstructure. At the same time, these materials generally show very high strength, although ductility or toughness may not be good. Strength increases as the microstructure scale reduces from the macro-micro level and even finer, but sometimes the strength appears to fall as the structure scale approaches the nano level. These strength variations are examined here, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 70 publications
1
13
0
3
Order By: Relevance
“…6 Electron back-scattering diffraction (EBSD) study of deformed materials is nowadays used for understanding the heterogeneity of plastic deformation in polycrystalline materials and also for estimating plastic strain in deformed materials. 7,8 Using EBSD technique, considerable amount of investigations have already been performed to understand the development of intragranular misorientation because of heterogeneous nature of plastic deformation in different materials. From these investigations, it is observed that the average misorientation (grain, kernel and local) increases linearly with increase in the amount of macroscopic plastic strain.…”
Section: Introductionmentioning
confidence: 99%
“…6 Electron back-scattering diffraction (EBSD) study of deformed materials is nowadays used for understanding the heterogeneity of plastic deformation in polycrystalline materials and also for estimating plastic strain in deformed materials. 7,8 Using EBSD technique, considerable amount of investigations have already been performed to understand the development of intragranular misorientation because of heterogeneous nature of plastic deformation in different materials. From these investigations, it is observed that the average misorientation (grain, kernel and local) increases linearly with increase in the amount of macroscopic plastic strain.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclean en juntas de grano o juntas de macla previas y crecen atravesando los granos austeníticos hasta que son interrumpidas por otras juntas de alto ángulo (junta de grano u otra banda de macla) u otro tipo de obstáculos como precipitados o inclusiones. La proliferación de las maclas mecánicas determina la subdivisión progresiva de los granos austeníticos originales en finos dominios delimitados por juntas de maclas (que son juntas de fuerte desorientación, 60°), dando lugar a un proceso físico de endurecimiento por deformación que constituye un mecanismo de endurecimiento dinámico de HallPetch (Morris, 2010).…”
Section: Introductionunclassified
“…Se presenta la microdureza promedio, la determinada en los carboboruros Mo/W y en el eutéctico. Puede verse que los valores de microdureza promedio se encontraron entre 800 y 970 HV 2 , mostrando una disminución con el aporte térmico [19,22,23]. Esto estaría asociado con la variación de la microdureza de las fases.…”
Section: Microdurezaunclassified